2017
DOI: 10.1038/s41598-017-13381-5
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq transcriptome profiling of mouse oocytes after in vitro maturation and/or vitrification

Abstract: In vitro maturation (IVM) and vitrification have been widely used to prepare oocytes before fertilization; however, potential effects of these procedures, such as expression profile changes, are poorly understood. In this study, mouse oocytes were divided into four groups and subjected to combinations of in vitro maturation and/or vitrification treatments. RNA-seq and in silico pathway analysis were used to identify differentially expressed genes (DEGs) that may be involved in oocyte viability after in vitro m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Recently, Smart-seq2 technology has been developed to analyze transcripts at a single cell level (Picelli et al, 2014 ). This technique has been successfully applied to detect the effect of vitrification on the transcriptome in mouse oocytes (Gao et al, 2017 ; Lee et al, 2019 ) and bovine oocytes (Wang et al, 2017 ; Huang et al, 2018 ). In particular, by using the Smart-seq2 technique, it was found that vitrification mainly affected apoptosis in mouse oocytes (Lee et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Smart-seq2 technology has been developed to analyze transcripts at a single cell level (Picelli et al, 2014 ). This technique has been successfully applied to detect the effect of vitrification on the transcriptome in mouse oocytes (Gao et al, 2017 ; Lee et al, 2019 ) and bovine oocytes (Wang et al, 2017 ; Huang et al, 2018 ). In particular, by using the Smart-seq2 technique, it was found that vitrification mainly affected apoptosis in mouse oocytes (Lee et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have examined the transcriptome in individual injected oocytes and compared it to that from non-injected oocytes 17 . Transcriptome analysis of single oocytes has been reported in various species including mouse, cow and man [29][30][31] . We detected approximately 10,600 genes as being expressed in bovine oocytes, which is similar to what has been reported previously 30,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…In animals, from diverse models, four studies have used global transcriptomic analyses (i.e. RNA-sequencing) [125][126][127][128] (Table 4). In a murine model, Gao et al found no differences between vitrified and fresh oocytes [125].…”
Section: Impact Of Oocyte Vitrification On Gene Expressionmentioning
confidence: 99%
“…RNA-sequencing) [125][126][127][128] (Table 4). In a murine model, Gao et al found no differences between vitrified and fresh oocytes [125]. On the contrary, differentially expressed genes were found in bovine and porcine oocytes [126][127][128].…”
Section: Impact Of Oocyte Vitrification On Gene Expressionmentioning
confidence: 99%